Electricity generation from living plants using microbial fuel cells - Mohnish, Borker; T.V, Suchithra (International Journal of Engineering and Technology, 2018)
The need for a sustainable source of energy has catered engineers to discover and develop a biological battery known as Plant Microbial fuel cell. This biological battery operates with the help of electrochemically active bacteria in presence of CO2, sunlight and water. This technique is gaining importance in the field of bioelectricity as it produces clean in-situ energy from living plants without the need to harvest the plant species. Research on these cells have led to the development of various models. One such plant species Setaria faberi was tested for its compatibility in sediment plant microbial fuel cell. Power density of 4.6mW/m2 was obtained when it was tested with cocopeat as a hydroponic media. This paper highlights the suitability of S. faberi in producing sustainable bioelectricity with a hydroponic media.Â Â